The use of acetylcholinesterase inhibition in river snails (Sinotaia ingallsiana) to determine the pesticide contamination in the upper Ping River - Chitmanat C. (2014)
The purpose of this study was to monitor the organophosphorus and carbamate pesticide contamination in an aquatic environment using the indigenous river snail (Sinotaia ingallsiana) as the bioindicator. This study was carried out from October 2006 to March 2007. The river snails were dipped in the Ping River in the Chiangmai area, where agricultural sites are densely located. One day after exposure, the samples were sacrificed for the determination of acetylcholinesterase activity. Results indicated that the AchE activity in the river snails collected from several sites of the Ping River was lower than control specimens kept in laboratory. In rainy season, un-exposed snails exhibited significantly higher AChE activity (P < 0.05) than the other three specimens derived from contaminated sites (9.4740, 1.0450, 1.0428 & 1.6002 μmole min-1 g-1 tissue, respectively). The AChE activity showed seasonal differences with minimum activities during the winter period. Therefore the AChE activity of the river snail could be considered as a good early indicator of pesticide contamination in an aquatic environment. Besides AChE activity, the other biochemical markers as well as histopathology effects, growth, reproduction and survival of aquatic organisms living in these contaminated areas have also been determined.